Internalized stigma level, family self-stigma, and family burden of patients receiving community mental health center services: a comparative, longitudinal study - Tozoğlu, Elif Özcan; Gürbüzer, Nilifer (Frontiers in Psychiatry, 2024)
IntroductionThe study aimed to evaluate, both comparatively and longitudinally, the effects of receiving services from community mental health centers on the stigma levels of patients and relatives and the burden of care for patients with severe mental illness.MethodsThe study was planned to be conducted on patients with severe mental illness [schizophrenia spectrum disorders (SSDs) and bipolar disorder (BD)] and their relatives, followed by the community mental health center (CMHC group) and the outpatient clinic (outpatient group). It was planned to provide psychoeducation to relatives once a month for 2 h; meetings with the case manager at least once every 2 weeks; and psychosocial interventions (social inclusion, daily life activities studies, etc.) and psychoeducation for 2 h once a week for the patients. The Internalized Stigma of Mental Illness Scale (ISMI) was applied to the patients; the Zarit Caregiver Burden Scale (ZCBS) and the Self-Stigma Inventory for Families (SSI-F) were applied to the relatives at the beginning of the study, at the 6th and 12th month.ResultsThe study was completed with 53 patients from the CMHC group (number of patients with SSDs = 39, number of patients with BD = 14) and 60 patients from the outpatient group (number of patients with SSDs = 45, number of patients with BD = 15). In the CMHC group, in patients with SSD, there was a statistically significant decrease in ISMI (p < 0.001), ZCBS (p < 0.001), and SSI-F (p < 0.001) scores at the end of the 12th month. In the outpatient group, in patients with SSD, there was no statistically significant decrease in ISMI (p = 0.948), ZCBS (p = 1.000), and SSI-F (p = 1.000) scores at the end of the 12th month. In the CMHC group, in patients with BD, there was a statistically significant decrease in ISMI (p = 0.002), ZCBS (p < 0.001), and SSI-F (p < 0.001) scores at the end of the 12th month. In the outpatient group, in patients with BD, there was no statistically significant decrease in ISMI (p = 0.645), ZCBS (p = 0.166), and SSI-F (p = 0.142) scores at the end of the 12th month.DiscussionThe results of our study suggest that multidimensional assessments of patients and their families, efforts to promote social participation, support for self-management in daily life, and psychoeducation may be helpful in reducing stigma and burden.